Perancangan Aplikasi Penyedia Produk Digital Berbasis Website - Salahudin Robo; Rasna; Siti Marwa (JSAI (Journal Scientific and Applied Informatics), 2022)
The marketing media specifically marketed digital products in the city of jayapura remain very scarce for free, so the digital product from creator-creator in jayapura does not reach its appropriate market target and causes its lack of technical implementation from creators. The study used the method of analysis at pieces to identify the differences and influences provided by the proposed system. With six indicators of spectacle, information and data, economy, control and security, integration and service. The result is a web-based digital product provider application. The application gains an average value of satisfaction (rk) involving 16 respondents with the following value acquisition: at the performance indicator: 4.5 which means "satisfied," economic indicator: 4.4 which means "satisfied," control indicator: 4.5 which means "satisfied" indicator: 4.3 which means "satisfied" and service indicator: 4.4 which means "satisfied." And thus it can be said that: "user satisfaction with the digitized applications" belongs in the satisfied category